Reflexões e possibilidades sobre a quantificação dos surdos sinalizantes nos levantamentos censitários brasileiros - Lima, João Víctor de Araujo (Universidade Federal de São Carlos, 2023)
Brazilian deaf individuals face a series of challenges in their daily lives, especially regarding the guarantee of their linguistic rights, even after the legal recognition of Brazilian Sign Language in 2002. A relevant aspect to be considered is how they are represented in the official statistics of the country's census surveys, which play a fundamental role in the production and monitoring of Brazilian public policies. From this context, the objective of this research was to identify how deaf signers are currently quantified in the statistics of the Brazilian Institute of Geography and Statistics (IBGE) and present possible paths for a dialogue that allows for the inclusion of the demands of deaf social movements in the population statistics research in Brazil. To accomplish this, the study is based on the concept of dual category status of deaf individuals and sign languages, in order to understand the impact of different conceptions of deafness in the census surveys conducted by IBGE, and on the concept of statactivism, through the approach of the sociology of quantification, to facilitate a dialogue between the demands of these movements and the institute. In general, mentions of “deaf individuals” and “sign languages” were analyzed in: 1) Claims made by Brazilian deaf individuals; 2) IBGE statistics, mainly in the Demographic Census and the National Health Survey. In addition, the statistical activism of indigenous peoples in IBGE's statistics was studied, seeking inspiration for Brazilian deaf statactivism. Based on these analyses, the study results indicate that there has been an evolution in the conception of deaf individuals in Brazilian census surveys, but they are still represented solely as people with disabilities. To incorporate the demands of deaf communities into these surveys, national and international partnerships with academics and international organizations responsible for statistical production are essential, incorporating the socio-anthropological perspective on deaf individuals, as well as constant dialogues between deaf representations such as Feneis and the World Federation of the Deaf, and IBGE.
Reflections and possibilities on the quantification of signing deaf individuals in brazilian census surveys
Keywords: Educação especial; Surdos; Libras; Dupla categorização; Pesquisas censitárias; Special education; Deaf; Brazilian sign language; Dual category status; Census survey research; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS SOCIAIS APLICADAS::DEMOGRAFIA::FONTES DE DADOS DEMOGRAFICOS; CIENCIAS SOCIAIS APLICADAS::DEMOGRAFIA::POLITICA PUBLICA E POPULACAO; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO